Effects of submaximal and supramaximal accentuated eccentric loading on mass and function - Maroto-Izquierdo, Sergio; Martín-Rivera, Fernando; Nosaka, Kazunori; Beato, Marco; González-Gallego, Javier; de Paz, José A. (Frontiers in Physiology, 2023)
Eccentric-overload (EO) resistance training emerges as an alternative to more optimally prescribe intensity relative to the force generation capabilities of the eccentric muscle contraction. Given the difficulties to individually prescribe absolute eccentric loads relative to each person's eccentric ability, setting the load relative to the concentric one-repetition maximum (1-RM) is the most used EO training approach. Therefore, we investigated the effects of submaximal and supramaximal (i.e., eccentric loads above 100% of 1-RM) accentuated eccentric training on changes in lean mass, anabolic hormonal responses and muscle function. Physically active university students (n=27) were randomly assigned to two training groups. Participants in the training groups performed dominant leg isotonic training twice a week for 10 weeks (4 sets of 8 repetitions). Isotonic resistance was generated by an electric-motor device at two different percentages of 1-RM for the eccentric phase; 90% (submaximal load, SUB group) and 120% (supramaximal load, SUPRA group). Concentric load was the same for both groups (30% of 1-RM). Changes in total thigh lean mass (TTLM), anabolic hormonal responses (growth hormone, IGF-1, IL-6, and total testosterone), unilateral leg-press 1-RM, maximal voluntary isometric contractions (MVIC), local muscle endurance (XRM), muscle power at 40 (PP40), 60 (PP60) and 80% (PP80) of the 1-RM, and unilateral vertical jump height before and after training were compared between groups. After training, both SUB and SUPRA groups showed similar increases (p<0.05) in MVIC (19.2 and 19.6%), XRM (53.8 and 23.8%), PP40 (16.2 and 15.7%), TTLM (2.5 and 4.2%), IGF-1 (10.0 and 14.1%) and IL-6 (58.6 and 28.6%). However, increases in 1-RM strength (16.3%) and unilateral vertical jump height (10.0–13.4%) were observed for SUPRA only. Indeed, SUPRA was shown to be more favorable than SUB training for increasing 1-RM (ES=0.77 [1.49-0.05]). Unilateral muscle power at medium and high intensity (10.2 and 10.5%) also increased in SUB but without significant differences between groups. Therefore, similar functional and structural effects were demonstrated after 10 wk EO training with submaximal and supramaximal eccentric loads. Although supramaximal loading might be superior for increasing 1-RM, the use of this approach does not appear to be necessary in healthy, active individuals.